Atmospheric effects on free space earth-to-satellite optical link in tropical climate - M.Nor, Norhanis Aida; Islam, Md Rafiqul; Al-Khateeb, Wajdi Fawzi Mohammed; Ahmad Zabidi, Suriza (International association of Academicians, Scholars, Scientists & Engineers (IAASSE), 2013)
Free Space Optic (FSO) vulnerability towards atmospheric phenomena is becoming a main issue towards its implementation. A lot of studies have been conducted to estimate the climatological effects on FSO links but most of them are based on terrestrial link with short path lengths and centred in temperate regions.Hence, this paper aims to analyse the performance of FSO links from earth-to-LEO satellite in tropical regions where rain and haze are the main concerns. This analysis is based on available methods and data to predict earth-to-satellite FSO links with the scaled up data from the measurement on terrestrial FSO link installed at International Islamic University Malaysia (IIUM) Kuala Lumpur campus. Data collected from terrestrial link are FSO received signal levels, corresponding rain intensity and visibility variations. The measured data are scaled up to the effective distance of slant path lengths and then compared with the predicted values. These findings will be very useful for FSO earth-space communication link designers and can be as a benchmark of FSO system design.